CO2 emissions, economic growth, and the environmental Kuznets curve in China: What roles can nuclear energy and renewable energy play?. (20th September 2018) - Dong, Kangyin; Sun, Renjin; Jiang, Hongdian; Zeng, Xiangang
Abstract: The aim of this study is to investigate the dynamic causal links among per capita carbon dioxide (CO2 ) emissions, per capita gross domestic product (GDP), per capita fossil fuels consumption, per capita nuclear energy consumption, and per capita renewable energy consumption within the framework of the environmental Kuznets curve (EKC) for the case of China. To do so, a series of econometric techniques allowing for structural break is utilized for the period of 1993–2016. The empirical results confirm the existence of the EKC for CO2 emissions in China. The estimated turning point (TP) of China's EKC for CO2 emissions is calculated as 96, 680.47 yuan and is expected to reach its peak by approximately 2028. The empirical results also indicate that, in both the short and long run, nuclear energy and renewable energy play important roles in mitigating CO2 emissions, while fossil fuels consumption is indeed the dominant culprit for promoting CO2 emissions. Furthermore, the mitigation impact of nuclear energy consumption on CO2 emissions is considerably smaller than that of renewable energy consumption, implying that renewable energy will be the main contributor to CO2 emissions mitigation in China. Finally, several important policy implications for mitigating China's CO2 emissions and promoting growth in the nuclear energy and renewable energy industries are provided. Highlights: The study confirms the existence of the EKC for CO2 emissions in the long run. The turning point of EKC is calculated as 96, 680.47 yuan. The EKC is expected to reach its peak by approximately 2028. Nuclear energy and renewable energy consumption can lead to less CO2 emissions.